Daxx and HIRA go viral – How chromatin remodeling complexes affect DNA virus infection - Julia Mai; Masih Nazari; Thomas Stamminger; Sabrina Schreiner (Tumour Virus Research)
Daxx and HIRA are key proteins in the host response to DNA virus infections. Daxx is involved in apoptosis, transcription regulation, and stress responses. During DNA virus infections, Daxx helps modulate the immune response and viral progression. Viruses like adenoviruses and herpesviruses can exploit Daxx to evade immune detection, either by targeting it for degradation or inhibiting its function. Daxx also interacts with chromatin to regulate transcription, which viruses can manipulate to enhance their own gene expression and replication. HIRA is a histone chaperone and reported to be essential for chromatin assembly and gene regulation. It plays a critical role in maintaining chromatin structure and modulating gene accessibility. During DNA virus infection, HIRA influences chromatin remodeling, affecting both viral and host DNA accessibility, which impacts viral replication and gene expression. Additionally, the histone variant H3.3 is crucial for maintaining active chromatin states. It is incorporated into chromatin independently of DNA replication and is associated with active gene regions. During viral infections, H3.3 dynamics can be altered, affecting viral genome accessibility and replication efficiency. Overall, Daxx and HIRA are integral to orchestrating viral infection programs, maintaining latency and/or persistence, and influencing virus-induced transformation by modulating chromatin dynamics and host immune responses, making them significant targets for therapeutic strategies once fully understood. Here, we summarize various DNA viruses and their crosstalk with Daxx and HIRA.